Down Staging of Cirrhosis in All Cirrhotic Patients with HCV Genotype 3-a Infection, Treated with 12-Weeks Triple Therapy, Including Sofosbuvir, Daclatasvir and Ribavirin (Medical Forum Monthly, 2024)
Objective: This study was mainly conducted to assess the improvement in the stages of cirrhosis in all treated patients with HCV genotype 3a infection, treated with triple therapy including daclatasvir, sofosbuvir and ribavirin in population of Khyber Pakhtunkhwa.Study Design: Prospective longitudinal study.Place and Duration of Study: This study was conducted at the Department of Pharmacology, Khyber Medical College and Khyber Teaching Hospital Peshawar from May 2017 to October 2017.Materials and Methods: Total of 75 cirrhotic patients with HCV genotype-3a infection, were enrolled and were assigned into 02 groups including group-I as those having Child Pugh Turcott stage-C cirrhosis and group-II as those having Child Pugh Turcott stage-B cirrhosis. Daclatasvir, Sofosbuvir and ribavirin was given for 12-weeks. Child Pugh Turcotte (CPT) staging was done before and after the completion of 12-weeks treatment. The primary end point was end of treatment (EOT-12) response with 12-weeks therapy, which is defined as HCV RNA level<40IU/ml after 12-weeks of therapy and improvement in the stages of cirrhosis.Results: Out of total 75 liver cirrhotic genotype 3a infected patients 44 (58.7%) were males while 31 (41.3%) were females. Their mean age is 50.95 ± 8.58 years. According to the CPT staging criteria, 40 (53.3%) patients with stage-C (group-I) while 35 (46.7%) patients with stage-B (group-II). At the end of therapy, 15% and 62.5% of the patient in group-I were down staged from C to A and C to B respectively. Similarly, in group-II, 57.1% of total patients were down staged from stage-B to stage-A.Conclusion: Triple therapy including Daclatasvir, Sofosbuvir and ribavirin is not only effective in all cirrhotic patients with chronic hepatitis-C genotype-3a infections, but also improve the clinical parameters and stages of cirrhosis.